2009
DOI: 10.2460/javma.234.11.1432
|View full text |Cite
|
Sign up to set email alerts
|

Tendinitis of the proximal aspect of the superficial digital flexor tendon in horses: 12 cases (2000–2006)

Abstract: Tendinitis of the proximal portion of the SDFT was a cause of lameness in aged performance horses; prognosis for return to previous use was poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…8,10 In comparison, the data obtained in the present study indicated that 14 (82%) of the cutting horses with SDF tendonitis returned to training and only 3 (18%) of them had recurrence of tendon lesions. On the basis of the results of the present retrospective study, the prognosis for cutting horses with SDF tendonitis is much better than that for affected racehorses.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…8,10 In comparison, the data obtained in the present study indicated that 14 (82%) of the cutting horses with SDF tendonitis returned to training and only 3 (18%) of them had recurrence of tendon lesions. On the basis of the results of the present retrospective study, the prognosis for cutting horses with SDF tendonitis is much better than that for affected racehorses.…”
Section: Discussionmentioning
confidence: 39%
“…3 Most of the published data regarding SDF tendonitis in horses are associated with sport and racing disciplines, 4 with the lesion most commonly located in the center of the tendon within the mid-metacarpal region 5,6 (generating a classic core lesion appearance in ultrasonographic images). 4,[8][9][10][11] After tendon injury, the chances of affected racehorses returning to racing are < 50%, and of those that Superficial digital flexor tendonitis in cutting horses : 19 cases (2007-2011) Tyler E. Tipton, DVM; Chris S. Ray, DVM, DACVS; D. Reese Hand, DVM, DACVS Objective-To characterize superficial digital flexor (SDF) tendon lesions in the forelimbs of cutting horses and determine recurrence rate and prognosis for this condition. 7 Tendonitis of the SDF in horses other than cutting horses is commonly considered to have a poor prognosis with a high recurrence rate and is often a career-ending injury.…”
mentioning
confidence: 99%
“…Studies evaluating superficial digital flexor tendon injuries in older horses suggested that location of injury, independent of severity, was important in determining prognosis. Whereas older horses with severe injuries at the level of the midmetacarpus typically returned to their original use, those with abnormalities in the proximal third of the metacarpus or carpus were significantly more lame and carried a graver prognosis . While outcome was not reported in this study, the present results indicated that older horses were more at risk for injuries within the muscle and musculotendinous junction regions of the superficial digital flexor and they were significantly more lame than young horses.…”
Section: Discussioncontrasting
confidence: 60%
“…6,8,9,11 Lameness evaluation is a clinically relevant marker of orthopedic injury improvement and was used as our primary outcome as severe lesions in tendons, ligaments, and joints present with lameness as the main clinical sign. [13][14][15] Lameness grade improvement was observed for tendons (75%), ligaments (60%), concurrent tendon and ligament lesions (50%), and joints lesions (54.5%), showing the potential of MSC treatment for injury to these structures. The subjectivity of lameness evaluation is a potential source of information bias resulting from the expectations a clinician has to observe a positive response to the chosen therapy, as well as differences in interpretation and grading of lameness among veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…The subjectivity of lameness evaluation is a potential source of information bias resulting from the expectations a clinician has to observe a positive response to the chosen therapy, as well as differences in interpretation and grading of lameness among veterinarians. 16,17 Imaging techniques provide a more objective evaluation for diagnosis and lesion assessment, 15,[18][19][20] but present limitations such as cost, accessibility, and availability that become a drawback when used in retrospective studies as the sole outcome evaluation method. For this reason, improvement through imaging assessment was a secondary outcome in our investigation, and lesion improvement was found in all tissue types evaluated: tendons (83.3%), ligaments (75.0%), and joints (66.7%).…”
Section: Discussionmentioning
confidence: 99%